A comprehensive review on anticancer mechanism of bazedoxifene. (17th April 2021) - Zafar, Erum; Maqbool, Muhammad Faisal; Iqbal, Asia; Maryam, Amara; Shakir, Hafiz Abdullah; Irfan, Muhammad; Khan, Muhammad; Li, Yongming; Ma, Tonghui
Abstract: Cancer is counted as a second leading cause of death among nontransmissible diseases. Identification of novel anticancer drugs is therefore necessary for the effective treatment of cancer. Conventional drug discovery is time consuming and expensive process. Unlike conventional drug discovery, drug repositioning offers a novel strategy for urgent drug discovery since it is a cost‐effective and faster process. Bazedoxifene (BZA) is a synthetic selective estrogen receptor modulator, approved by the United States Food and Drug Administration for the treatment of osteoporosis in postmenopausal women. BZA is now being studied for its anticancer activity in various cancers including breast cancer, liver cancer, pancreatic cancer, colon cancer, head and neck cancer, medulloblastoma, brain cancer, and gastrointestinal cancer. Studies have reported that BZA is effective in reducing cancer progression through multiple mechanisms. BZA could effectively inhibit STAT3, PI3K/AKT, and MAPK signaling pathways and induce apoptosis. In addition to its anticancer activity as monotherapy, BZA has been shown to enhance the chemotherapeutic efficacy of clinical drugs such as paclitaxel, cisplatin, palbociclib, and oxaliplatin in multiple neoplasms. This review mainly focused on the anticancer activity, cellular targets, and anticancer mechanism of BZA, which may help the further design and conduct of research and repositioning it for oncological clinic trials.